The Source of Open-Source Culture: Participation in the Production of an Open Media Artifact, Minecraft - Leavitt, Alex (AoIR Selected Papers of Internet Research, 2013)
How does an open, participatory media artifact evolve in relation to participants’ perceptions of it? Scholars have heralded participatory culture as the next advance in the construction of media artifacts, though few researchers have delved into the discussions, boundary-making, and motivations of produsers’ participation in iteratively-created open media. Through interpretation in grounded theory and extended case method analysis of ethnographic participant observation and interviews, this paper examines Minecraft, a video game that became popular during its development, through which players contributed ancillary content that eventually impacted the game’s official development. By examining players’ and modders’ perceptions of official- and player-produced content for the game, this paper demonstrates how value emerges from open, participatory media artifacts and how levels of participation produce different experiences with the game. By detailing the dynamics underlying participatory cultures, we can begin to further understand how collaboration and conflict operate in “open-source culture.”